Analysis of the microscopic mechanism of coal wettability evolution in different metamorphic states based on NMR and XPS experiments. Issue 76 (12th October 2017) - Xu, Cuicui; Zhou, Gang; Qiu, Han
Abstract : To investigate the evolution of carbon- and oxygen-containing groups during metamorphism and the influence of the structural variation of coal on its wettability, NMR and XPS were employed to study the two main elements, carbon and oxygen, in coal dust. Abstract : To investigate the evolution of carbon- and oxygen-containing groups during metamorphism and the influence of the structural variation of coal on its wettability, NMR and XPS were employed to study the two main elements, carbon and oxygen, in coal dust. Our results show that with an increase of the metamorphic degree, the number of highly reactive hydroxyl and carboxyl groups show a descending trend whereas the number of low reactivity ether and carbonyl groups increases. The number of carbon-containing groups gradually increases when the metamorphic degree increases, due to a clustering change process which includes an increase in the number of aromatic carbons (Ar-C, H) and a simultaneous decrease in the number of carboxyl carbons (–COOH), methylene carbons (CH2 ) and ether based carbons (Ar-O, R–O). The reduction rate of carboxyl carbon (–COOH) is closest to the growth rate of aromatic carbon (Ar-C, H). The methyl (CH3 ) and carboxyl (CO) carbon evolve discontinuously with the metamorphic degree, which is different from the other carbon groups. Linear-regression analysis suggests that the correlation coefficients between aromatic (Ar-C, H), ether (R–O), methylene (CH2 ) and carboxyl (–COOH) carbons and wettability are 0.98, 0.97, 0.96 and 0.92, respectively, indicating that the main contribution to the wettability from carbon-containing groups comes from these groups. In contrast, hydroxyl oxygen (–OH) has a correlation coefficient as high as 0.98, and is a major contributor from the oxygen-containing groups.